Effects of Child and Maternal Histo-Blood Group Antigen Status on Symptomatic and Asymptomatic Enteric Infections in Early Childhood. (15th February 2019) - Colston, Josh M; Francois, Ruthly; Pisanic, Nora; Peñataro Yori, Pablo; McCormick, Benjamin J J; Olortegui, Maribel Paredes; Gazi, Md Amran; Svensen, Erling; Ahmed, Mondar Maruf Moin; Mduma, Esto; Liu, Jie; Houpt, Eric R; et al.
Abstract: Background: Histo-blood group antigens (HBGAs) such as fucosyltransferase (FUT)2 and 3 may act as innate host factors that differentially influence susceptibility of individuals and their offspring to pediatric enteric infections. Methods: In 3 community-based birth cohorts, FUT2 and FUT3 statuses were ascertained for mother-child dyads. Quantitative polymerase chain reaction panels tested 3663 diarrheal and 18 148 asymptomatic stool samples for 29 enteropathogens. Cumulative diarrhea and infection incidence were compared by child (n = 520) and mothers' (n = 519) HBGA status and hazard ratios (HRs) derived for all-cause diarrhea and specific enteropathogens. Results: Children of secretor (FUT2 positive) mothers had a 38% increased adjusted risk of all-cause diarrhea (HR = 1.38; 95% confidence interval (CI), 1.15–1.66) and significantly reduced time to first diarrheal episode. Child FUT2 and FUT3 positivity reduced the risk for all-cause diarrhea by 29% (HR = 0.81; 95% CI, 0.71–0.93) and 27% (HR = 0.83; 95% CI, 0.74–0.92), respectively. Strong associations between HBGAs and pathogen-specific infection and diarrhea were observed, particularly for noroviruses, rotaviruses, enterotoxigenic Escherichia coli, and Campylobacter jejuni / coli . Conclusions: Histo-blood group antigens affect incidence of all-cause diarrhea and enteric infections at magnitudes comparable to many common disease control interventions. Studies measuring impacts of interventions on childhood enteric disease should account for both child and mothers' HBGA status. Abstract : The histo-blood group antigens of children and their mothers are determinants of diarrhea in early childhood. This study estimates the innate immunity provided by HBGA for principal etiologies of diarrhea and demonstrates altered risk for bacterial and viral enteropathogens.